Celebrity anti-Semitism – A translation studies perspective. (November 2015) - Weissbrod, Rachel
Abstract: This paper deals with offensive anti-Semitic remarks made by celebrities and public figures, which led to scandals that were reported in online newspapers, magazines, and other news websites. The texts investigated were originally written in Hebrew, but they contain a translational component – anti-Semitic slurs translated into Hebrew and marked as direct speech, usually by the use of quotation marks. The paper points out two tendencies that were detected in the Hebrew reportage: explicitation, accentuation, and intensification, on the one hand, and humorous framing – especially when dealing with the world of entertainment – on the other hand. The first tendency, which is apparent in the translations themselves, has been discerned in the rendering of slurs which are "voids, " according to the terminology of translation studies, and in the translation of other slurs as well. It is consistent with what translation studies labels "universals of translation"– phenomena entailed by the very process of inter-lingual transfer. This tendency is also in line with the attraction of some journalistic writing for the sensational. A less universal explanation for the intensification of anti-Semitic slurs is an inclination toward self-victimization on the part of the target culture. The second tendency – humorous framing of the translated utterances– can be interpreted as a means of coping with anti-Semitic slurs; by employing their sense of humor, the writers demonstrate superiority over those who use them. The two tendencies combine (not necessarily in the same reportage) to magnify verbal anti-Semitism, and then defeat it by using humor. Through this case-study, this paper offers several contributions: 1) Discussing slurs from the point of view of translation – which is a contribution to both translation studies and the study of slurs; 2) Applying the concepts of voids, explicitation and intensification, which have been developed in translation studies, to the study of slurs; 3) Investigating slurs in the context of journalism; 4) Pointing out the use of humor as a means to cope with slurs; 5) Addressing the issue of anti-Semitism from a unique perspective, combining translation, slurs, humor and journalism. Highlights: Anti-Semitic slurs by celebrities are discussed in the context of translation. The slurs are the topic of Hebrew reportage published online. Slurs which are voids, and other slurs, have been explicitated and intensified. Humorous framing has been used as a protection mechanism. The two tactics combine to increase the threat and defeat it by using humor.